1998
DOI: 10.3892/ijmm_00000076
|View full text |Cite
|
Sign up to set email alerts
|

Thymidylate synthase, dihydropyrimidine dehydrogenase, orotate phosphoribosyltransferase mRNA and protein expression levels in solid tumors in large scale population analysis

Abstract: Abstract. It has been reported that the expression of thymidylate synthase (TS), dihydropyrimidine dehydrogenase (DPD) and orotate phosphoribosyltransferase (OPRT) may predict the clinical efficacy of 5-fluorouracil (5-FU)-based therapy in cancer patients. We investigated the differences in the mRNA and protein expression of these enzymes in various tumor tissues. A total of 17,613 specimens of head and neck, gastric, colorectal, breast, lung and pancreatic cancer were collected from multiple facilities in Jap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 9 publications
(11 reference statements)
0
9
0
Order By: Relevance
“…5,[20][21][22] Regarding the sensitivity of TS in gastric cancer and colorectal cancer, sporadic reports have shown no correlation or reverse correlation between the sensitivity to 5-FU and increased TS activity. 23,24 In NSCLC, a positive correlation with TS was reported, but TS activity tends to be lower than in other carcinomas, 14 suggesting that even if TS activity is high, it falls within the range where the effect of 5-FU can be observed.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…5,[20][21][22] Regarding the sensitivity of TS in gastric cancer and colorectal cancer, sporadic reports have shown no correlation or reverse correlation between the sensitivity to 5-FU and increased TS activity. 23,24 In NSCLC, a positive correlation with TS was reported, but TS activity tends to be lower than in other carcinomas, 14 suggesting that even if TS activity is high, it falls within the range where the effect of 5-FU can be observed.…”
Section: Discussionmentioning
confidence: 99%
“…5-FU is rapidly degraded by DPD. Due to the higher DPD activity in NSCLC compared to other carcinomas, 14 5-FU alone is less effective, necessitating co-administration of CDHP, for which S-1 was developed. In view of the mechanism of action of 5-FU, the effects of 5-FU are expected to be reduced if expression of the target enzyme TS and the degrading enzyme DPD in tumor tissue is high.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, a pooled analysis of S-1 trials found that there was no difference in response to S-1 in combination with cisplatin depending on histological type (Yamamoto et al, 2010). Lung cancer showed relatively high expression of DPD, which causes greater degradation of 5-FU than other cancers (Fukui et al, 2008). Therefore, being a DPD-inhibitory fluoropyrimidine, S-1 might prevent overexpression of TS, which would make it a good candidate for the treatment of squamous cell carcinoma.…”
Section: Histology and S-1mentioning
confidence: 99%